Pokazateli sorevnovatel'noj intensivnosti i raschoda kalorij basketbolistok v igrach rossijskoj superligi i Vostocnoevropejskoj ligi v tecenie sezona - Lenshina, M. V.; Andrianova, R. I.; Fedoseev, D. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The analysis of the intensity of competitive activity is important for determining the load parameters and game modes in the training process. Skilled basketball players perform in a large number of the game matches during the season, but often, the data of the single game or tournament is analyzed. The article presents the data obtained as a result of the analysis of all games played for the 2018-19 season in the Russian Super League and Eastern European League (EWBL) by the Rostov-Don-SFU team, which became the champion and bronze medalist of these competitions.